Stalking victimization in Portugal: Prevalence, characteristics, and impact - Matos, M.; Grangeia, H.; Ferreira, C.; Azevedo, V.; Gonçalves, M.; Sheridan, Lorraine (2019)
Although the prevalence and associated features of stalking are well known in some countries, in many others, including Portugal, the experiences of stalking victims have remained unexplored until recently. This study aimed to identify the prevalence, characteristics, and impact of stalking victimization within a Portuguese population. A national community sample (N = 1210) took part in face-to-face interviews based on the Stalking Victimization Inventory. Lifetime prevalence of stalking was 19.5%. The type of relationship between the victim and the stalker was one of the main predictors of stalking diversity and duration (the closer the relationship, the greater the diversity and duration). The stalking impact was higher in victims that experienced more diverse stalking behaviours and fear. We also concluded that fear and impact mediate the relationship between stalking diversity and helpseeking. Results demonstrate that stalking victimization significantly affects the Portuguese population.